A mutant strain of Aspergillus nidulans is hypersensitive to cycloheximide - N. Babudri; G Morpurgo (Fungal Genetics Reports, 1995)
We routinely use a strain derived from the master strain A513 (FGSC) for mitotic linkage studies in our laboratory. This strain carries the ActA1 mutation on linkage group III, which should confer resistance to actidione (trade name for cycloheximide). However, we have observed that our strain 513s is hypersensitive to actidione in comparison with a wild-type strain at the ActA1 locus (our collection).